PENGARUH PROFITABILITAS, NILAI PERUSAHAAN DAN KOMISARIS INDEPENDEN TERHADAP PERATAAN LABA DALAM PERSPEKTIF AKUNTANSI SYARI’AH (Studi Kasus Pada Perusahaan Pertanian Yang Terdaftar Di Index Saham Syariah Indonesia (ISSI) Tahun 2020-2023) - Nugroho, Dimas; Hayati, Mardhiyah; Fajar Ramdani, Rahmat (Universitas Islam Negeri Alauddin Makassar, 2025)
Profit smoothing is a management practice carried out to smooth profit formats to create an impression of consistency before investors. However, from an Islamic perspective, this practice has the potential to violate the principles of honesty and trustworthiness. This study examines the influence of profitability, company value, and independent commissioners on income smoothing practices in Sharia accounting. The study population consisted of 10 agricultural companies measured by the Indonesian Sharia Stock Index (ISSI) during the period 2020 to 2023, and there were 8 samples that met the criteria for the propositional sampling technique. The method used was quantitative. Data analysis was performed using logistic regression with SPSS version 25, with income smoothing practices as the dependent variable. The research findings indicate that profitability and independent commissioners have no significant effect on income smoothing, while company value has a significant negative effect. These results indicate that external monitoring mechanisms through market perception are more effective than internal mechanisms in suppressing income smoothing practices. This study provides compulsion for companies to prioritize the principles of honesty and transparency in financial reporting that are aligned with Sharia values.